Berakhirnya Memorandum of Understanding Antara Pemerintah Indonesia dan Malaysia Tahun 2006 Tentang Domestic Workers Menurut Konvensi Wina 1969 - Eno Prasetiawan; Mexsasai Indra; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
The Government of Indonesia and Malaysia made an International treaty in the form of a Memorandum of Understanding (MoU) on Domestic Workers or about the recruitment and placement of Indonesian migrant Workers (TKI), especially domestic helpers (Housemaid) or so-called female workers informal sector in Malaysia in 2006 applicable 5 years. In practice, in 2009 Indonesia suspend implementation of the agreement to a moratorium on sending migrant workers to Malaysia for reasons of torture cases migrant workers in Malaysia. Furthermore, the MoU was amended in 2011 to change some settings on legal protection for migrant workers in Malaysia. As known in international law which applies the principle of pacta sunt servanda, where the agreement was binding and enforceable as a law for the parties.The problems posed in this paper is about the termination of the MoU Indonesia and Malaysia in point of view of the Vienna Convention 1969 and Indonesian Act No. 24 of 2000 about International Treaties, legal protection for workers contained in the MoU, and legal protection for workers after the expiry of the MoU. This research is a normative study, which examines the legal principle.From this research, it can be seen a few things. First, that the expiry of the MoU and amendment procedures are actually the MoU is in conformity with the agreement of the parties as to which is set also in the Vienna Convention of 1969 and Indonesian Act No. 24 of 2000 on International Treaties. Second, the legal protection for workers contained in the MoU is weak, because the MoU is set to a technical recruitment and placement of migrant workers and not paying attention more specifically on the protection of Indonesian migrant workers in Malaysia. Third, after the amendment of the MoU there are some changes for the better, but still not able to reach better legal protection for Indonesian domestic workers.Keywords: termination of the agreement, MoU, Indonesian Workers Protection Law.